First Love Never Dies - Aquino, Kaisa Rillorta (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
THE RADIO SCREECHED angrily before the volume adjusted to Tatay’s liking. From outside, I could only hear the familiar drumbeat— boom boom!—and the station’s signature line, “Basta radyoooo . . . Bombo!” I went inside, my eyes gradually adjusting to the darkness of the room. Tatay had taken off his shirt, more brown than white now, and wiped the sweat off his body. He sat down beside his small battery-powered radio. The fan whirred slowly. The afternoon expanded like a shallow pool of mud.